2020
DOI: 10.1021/acssuschemeng.0c02376
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity ofp-Coumaroyl Groups in Lignin upon Laccase and Laccase/HBT Treatments

Abstract: Laccase–mediator systems (LMS) are potential green tools for oxidative degradation and modification of lignin. Although LMS convert both phenolic and nonphenolic lignin structures, phenolic structures are more prone to react. Remarkably, in a previous study on laccase/HBT treatment of grasses, we observed the accumulation of p-coumaroyl moieties in residual lignin, even though such groups are free phenolic structures. To provide more insights into this apparent paradox, here, we studied the reactivity of p-cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Pine lignin showed a significant difference in structure, whereas G units dominated the aromatic region, and almost no signals of S units were observed in the NMR spectrum. Recent research reported that p -coumaric acid ( p CA) and ferulic acid (FA) moieties in cell walls of fast-growing grass biomass, functioning as cross-linking agents between lignin and carbohydrate moieties, could be etherified to the isolated lignin. The incorporation of p CA and FA moieties in corn cob lignin were noticeable, which could introduce readily cleavable ester bonds into the lignin structure, permitting easier depolymerization to produce monolignol p -coumarate conjugates . However, these two moieties were not evident in wood lignin, in particular, no signals were detected in pine lignin.…”
Section: Resultsmentioning
confidence: 99%
“…Pine lignin showed a significant difference in structure, whereas G units dominated the aromatic region, and almost no signals of S units were observed in the NMR spectrum. Recent research reported that p -coumaric acid ( p CA) and ferulic acid (FA) moieties in cell walls of fast-growing grass biomass, functioning as cross-linking agents between lignin and carbohydrate moieties, could be etherified to the isolated lignin. The incorporation of p CA and FA moieties in corn cob lignin were noticeable, which could introduce readily cleavable ester bonds into the lignin structure, permitting easier depolymerization to produce monolignol p -coumarate conjugates . However, these two moieties were not evident in wood lignin, in particular, no signals were detected in pine lignin.…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, Hilgers et al investigated in detail the reactivity of p -coumaroyl derivatives in lignin and model compounds in presence of laccase or a laccase-mediator system. 157 The use of (HBT) and N -hydroxyacetanilide (HPI), both being –N–OH type mediators, were found to be incorporated to lignin in presence of TvL or Pleurotus ostreatus laccase. 158 The grafting of these mediators may induce changes in the properties of lignin.…”
Section: Natural Polymers Modificationmentioning
confidence: 99%
“…Laccase possesses moderately high redox potentials of the active site T1 Cu center (0.42–0.79 V) and can oxidize, in principle, only phenolic residues of lignin directly. Thus, in most studies of laccase‐catalyzed lignin conversions, mediators have been used to mitigate the challenges associated with the large size of lignin and the high redox potential of the non‐phenolic reactions (Cañas & Camarero, 2010 ; Christopher et al, 2014 ; Hilgers et al, 2018 ; Hilgers, Kabel, et al, 2020 ; Hilgers, van Erven, et al, 2020 ; Rich et al, 2016 ; Zhu et al, 2020 ). Laccase catalyzes the one‐electron oxidation of the mediator to cation radicals which subsequently react with the high redox potential groups within bulky lignin.…”
Section: Introductionmentioning
confidence: 99%